Quality of 'Fuji' apples stored under controlled atmosphere and influence of climate on the incidence of internal browning Qualidade de maçãs 'Fuji' armazenadas em atmosfera controlada e influência do clima na degenerescência da polpa - Correa T.R.* (2010)
The objective of this work was to evaluate fruit quality and the relation between climatic conditions during fruit development and internal browning incidence under controlled atmosphere (CA) of storage, in 'Fuji' apples. Fruit from three orchards (Vacaria, RS, and São Joaquim and Lages, SC) and two years (2006/2007 e 2007/2008) were evaluated. The orchards were daily monitored, during fruit development, for minimum, medium and maximum temperatures, and for relative humidity and rainfall. Fruit were stored during eight months in different CA conditions, at -0.5±0,1°C and 97% relative humidity. Pearson's correlations between climatic condition variables and internal browning incidence after CA storage were estimated. Fruit stored under 1.2 kPa of O2 and 2.0 kPa of CO2 had higher titratable acidity, flesh firmness and texture, and lower respiration and ethylene production rates; however these fruit exhibited a high internal browning incidence in comparison to fruit stored at 1.2 kPa of O2 and <0.5 kPa of CO2. The internal browning incidence decreases as the medium daily temperatures occurred between 90 and 210 days after full bloom increase.